Results of the Graduates’ Satisfaction Survey (Journal of Interdisciplinary Insights, 2025)
Graduate satisfaction indicators are very important for improving and continuously developing the knowledge, skills, and attitudes required for the workplace of a good specialist, the content of the training program, the methodological environment, and the evaluation methodology. Studying the demand and supply of the labor market at the occupational level is of great importance for policy development. The issue of whether the newly qualified employees supplied by the educational institution are able to meet the requirements of the jobs available in the market is a topic related to graduate satisfaction.